Numerical study on flow and heat transfer of a hybrid microchannel cooling scheme using manifold arrangement and secondary channels - Yang, Min; Cao, Bing-Yang (Applied thermal engineering, 2019)
•A hybrid design using manifold arrangement and secondary channels for microchannel heat sink is proposed.•A Design Optimization Area (DOA) for the MMC-SOC is defined.•The pressure drop and thermal resistance can be both reduced in DOA.•The best hybrid design with geometrical parameters of (λ = 1, β = 1) is obtained. The flow and heat transfer characteristics of a novel hybrid microchannel heat sink with manifold arrangement and secondary oblique channels (MMC-SOC) are numerically studied. Through the relationship between the total thermal resistance ratio (Rt/Rt0) and pressure drop ratio (ΔP/ΔP0), we define a region named Design Optimization Area (DOA), where the pressure drop ΔP and the total thermal resistance Rt can be both reduced due to the secondary channels. The numerical results show that the best heat sink can reduce ΔP by 1.91%, and simultaneously decrease Rt by 19.15% compared to the original MMC heat sink at Re = 295. In addition, the effects of secondary channel on ΔP are dependent on both the geometrical parameters and Reynolds numbers. On the one hand, it can reduce the pressure loss at small Reynolds numbers for most heat sinks. However, it can also increase the pressure loss at high Reynolds numbers for most heat sinks. As Re increases, the ratio (Rt/Rt0) becomes smaller and (ΔP/ΔP0) becomes larger, indicating a better thermal performance and a worse hydraulic performance. The secondary flow field analyses visually show the hydraulic and thermal performance enhancements due to thermal boundary layer re-development and flow mixing.